Social and Health Dimensions in Museum’s Patronage and its Implications for Sustainable Livelihood (Journal of Management and Social Sciences, 2018)
Museums have been established as a veritable instrument for a virile tourism industrybecause of advantages inherent in them. Their potentials for showcasing the people andtheir culture is also a case that cannot be ignored. For the purpose of clarity, this paperhighlights the historical antecedents of museums in Nigeria with a view to helping inthe understanding of museum as a concept and that it is not alien to indigenous Africansocieties before the advent of the Europeans. It traces the development of modernmuseums in the colonial period, up to the present and notes the problems andassociated difficulties attached to the effective management and funding of museumsin Nigeria. Specifically, the paper investigates the community knowledge and attitudetowards Museums and its implication on sustainable livelihood in Ile-Ife City, withparticular focus on Ife National Museum. The study made use of questionnaire and indepthinterview to collect data from the study population. A total of 180 copies ofquestionnaire were retrieved from the respondents and analysed. The findings revealeda high level of awareness about the existence of Museums among the people and a lowlevel of patronage for leisure and tourism purposes, which implies poor appreciation ofits social and health benefits. This poor patronage was traced to poor appreciation ofculture, which inherently has implication on sustainable livelihood and developmentalprocesses. The need to address this consequently becomes apt in view of empiricaldeclaration that existing models of sustainable development forged from economic orenvironmental concern are unlikely to be successful without cultural considerations.KeywordsMuseums, knowledge, attitude, sustainable livelihood